THE PRODUCTION FACTORS OF CASSAVA CRACKER BUSINESS IN SUNGAI SAHURAI VILLAGE - Ilhami, M. Ridha; Fauzan, Akhmad; Hasanah, Mahmudah; Mutiani, Mutiani; Rusmaniah, Rusmaniah; Syaharuddin, Syaharuddin (International Conference On Social Science Education, 2024)
The research problem comes from the production factors of cassava crackers. This research aims to describe the production factors of the cracker business. The research used a qualitative method to describe the production factors of the cassava cracker business in Sungai Sahurai Village. Data were collected through observation, interviews, and documentation. Data analysis with data reduction refers to the research objectives, presentation of data obtained in the field, and conclusion. Testing data validity through triangulation and member check.  Based on the results of the study, it was found that the production activities of the cassava crackers business have several factors in the form of raw materials, capital, labour, and entrepreneurial skills. The primary raw material is cassava, capital whose source comes from its own and borrowed capital, labour, namely the business actors themselves, and additional labour and entrepreneurial skills that are passed down from generation to generation. This study concludes that in Sungai Sahurai Village, most of the residents have a cassava cracker business; these business activities can take place and still exist today because there are production factors that support each other.